UTILIZATION OF STUDENT PRESENCE INNOVATION USING BARCODE TO INCREASE DISCIPLINE IN SMPN 2 DLINGO - Safitri, Febri; Hasanah, Enung (EARR (Educational Administration Research and Review), 2020)
Discipline is the key to educational success. One indicator that shows the level of student discipline in the education process is the level of student participation in school. The presence of students in schools is closely related to achievement. Therefore, schools in Indonesia, continue to strive to achieve high levels. The use of presence by using barcodes is one of the educational innovations that is expected to improve student discipline so that student achievement increases. The purpose of this study is 1) To explore how the process of using presence by using a barcode; 2) discuss 1) how the attendance process is done by using a barcode in increasing student discipline; 2) Knowing the supporting factors of applying the presence of barcode in schools. 3) Knowing the inhibiting factors of the application of barcode barcodes in schools. This type of research is a descriptive study with qualitative. The research subjects were determined based on purposive sampling technique. The research subjects consisted of administrative staff, teachers, and students. Data collection techniques through interviews, observation, and documentation. The data collected is equipped with interactive deductive data analysis techniques that are collected collecting data, reducing data, presenting data, and completing conclusions. The results showed: 1) The process of implementing presence by using a barcode to improve student discipline is done by making a barcode on students, students do a barcode scan on each student, on direct barcode scanning automatically their expected name on the computer, while students who do not enter are written manually according to their description; 2) Supporting factors for the implementation of barcode initiatives in schools is that there is support from parents and all school members, in addition to that there are also infrastructure facilities such as barcode machines and electricity. 3) Inhibiting factors The application of barcodes in schools is a compilation that occurs due to power outages and damage to barcode machines, as well as when barcode guards are not present at school.